Muscle synergy during free throw shooting in basketball is different between scored and missed shots - Matsunaga, Naoto; Oshikawa, Tomoki (Frontiers in Sports and Active Living, 2022)
The current study investigated the differences in synergy during a free throw in basketball and compared synergies between scored and missed shots. Six men’s college basketball players participated in this study. A wireless electromyographic system was used to measure the activity of 16 trunk, upper and lower extremity muscles while completing the free throw. Three scored and missed shots were analyzed to extract the synergies using non-negative matrix factorization. Four synergies were extracted from the successfully made shots and three synergies were extracted for the missed shot. Two synergies were shared between scored and missed shots. The synergy that contributes to the shoulder flexion was used to set the ball and activate the initial stage of the free throw. Additionally, the synergy that contributes the palmar flexion was used to release the ball and activate the final stage of the free throw. The final synergy of the missed shot had both characteristics of the two synergies that one was extension of the lower limb in the midpoint of the shot and the other was extension the upper limb during the final stage of the shot observed in the scored shot. It is believed that these synergies that extend the lower and upper limb in scored shot activate in order to transfer the energy from the lower limb to the upper limb. In contrast, the synergy during the missed shot that may play a role in the failure due to the upper and lower limbs extended at same time.